PENOLAKAN PERMOHONAN PEMBATALAN PERKAWINAN KARENA SUAMI PENGIDAP HIV (ANALISIS PUTUSAN PENGADILAN AGAMA KOTA PARIAMAN NOMOR 610/PDTF.G/2019/PA.PRM): Refusal Of Application For Marriage Cancellation Due To Husband With Hiv (Analysis Of Decision Of Religious Court Of Kota Pariaman Number 610/Pdtf.G/2019/Pa.Prm) - Sahar, Mochamad Syafiq; Muriani (Faculty of Law, Universitas Trisakti, 2024)
Marriage can be done legally if it is done according to the provisions of the applicable law. If in a marriage there are things that do not comply with the provisions of Law No. 1 of 1974 concerning marriage and the Compilation of Islamic Law for those who are Muslim, then the marriage can be annulled. The main issues are 1) Can HIV be used as an excuse to cancel a marriage according to Law No. 1 of 1974 and the Compilation of Islamic Law? 2) Is the reason for rejecting the application for annulment of marriage in the decision Number 610/PdtF.G/2019/PA.Prm in accordance with Law No. 1 of 1974 and the compilation of Islamic law? The research method used is the normative juridical type, which is descriptive in nature. The data used is secondary data. The conclusion is drawn using deductive logic. The conclusions are 1) HIV/AIDS can be used as an excuse for annulling a marriage due to an oversight and misunderstanding of one of the partners so that the agreement becomes flawed and 2) the reason the judge refuses to annul a marriage is not in accordance with Law No. 1 of 1974, because HIV/AIDS AIDS is a contagious and very dangerous disease so that the goal of forming a happy and eternal family is not achieved. the judge should grant the request for annulment of the marriage by giving consideration because HIV/AIDS is based on the contra legem principle and the fiqh principles of dar' al-mafa muqoddam which should be an additional consideration for the judge in making a decision.